1985
DOI: 10.1002/1097-0142(19850415)55:8<1770::aid-cncr2820550825>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic chondroblastoma. Report of a fatal case with a review of the literature on atypical, aggressive, and malignant chondroblastoma

Abstract: A boy with metastatic and fatal chondroblastoma is presented. Unlike previously published examples of metastatic chondroblastoma, these metastases developed before any operative manipulation of the primary tumor. The histologic characteristics of the primary, metastatic, and locally recurrent tumors were those of a conventional chondroblastoma. A review of published cases of atypical, aggressive, and malignant chondroblastoma is presented with current follow‐up information. Although some metastatic chondroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(71 citation statements)
references
References 31 publications
1
66
0
4
Order By: Relevance
“…Third, given the exclusion of axial and aggressive tumors, our results of oncological outcome may also represent a best-case estimate of recurrence for patients with chondroblastomas overall. The incidence of metastasis secondary to chondroblastoma is not well defined in our study, but it is believed to occur rarely, in fewer than 1% of patients [12,22]. It is also possible that we did not detect possible metastases given our protocol of imaging post-treatment, which did not include routine chest CT scans at periodic intervals.…”
Section: Discussionmentioning
confidence: 84%
“…Third, given the exclusion of axial and aggressive tumors, our results of oncological outcome may also represent a best-case estimate of recurrence for patients with chondroblastomas overall. The incidence of metastasis secondary to chondroblastoma is not well defined in our study, but it is believed to occur rarely, in fewer than 1% of patients [12,22]. It is also possible that we did not detect possible metastases given our protocol of imaging post-treatment, which did not include routine chest CT scans at periodic intervals.…”
Section: Discussionmentioning
confidence: 84%
“…Metastases from chondroblastoma can arise from different primary sites. There is no reported relation of metastasis to previous surgery or nonsurgical treatment, tumour location, or patient age [7,25]. The lung is by far the most common site of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The lung is by far the most common site of distant metastases. Bones different from those of the primary site, soft tissue, the skin, and the liver are also cited [14,25]. The time reported for metastases to manifest clinically ranges from five months to 33 years (average, eight years) from the initial diagnosis of chondroblastoma [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the overall recurrence rate of benign tumors following curettage is less than 10% [1,2]. However, giant cell tumors or chondroblastomas require more careful management due to their high rate of recurrence [3,4]. Thus, local adjuvants should be considered to decrease the local recurrence rate in these cases.…”
Section: Introductionmentioning
confidence: 99%